Comparison of palliative care education for family caregivers in high-and-low-income countries: An integrative review - Martina Sinta Kristanti; Nurdina Wahyu Hidayati; Maryadi (Belitung Raya Foundation, Indonesia, 2023)
Background: In most resource-limited countries, palliative care is still under development. Despite the differences, the involvement of family caregivers is fundamental in both High-Income Countries (HICs) and Low-Income Countries (LICs). The lack of formal support in LICs implies that educational interventions to support family caregivers in this region could be more complex and urgently needed than in HICs. To comprehend the existing situation and identify the gaps in LICs, using HICs as a benchmark standard and conducting a review comparing educational interventions in both regions is essential. Objective: To identify and compare the existing implementation of education for family caregivers of patients with advanced cancer in LICs and HICs. Design: An integrative review guideline by Whittemore and Knafl was followed. Interventional studies related to education for family caregivers providing care for adult patients with cancer were included, and review articles were excluded. Data Sources: Data were obtained from PubMed, EBSCO, ProQuest, and ClinicalKey. The search was conducted on 18 November 2021 and updated on 9 August 2023. Review methods: Data reduction, data comparison, conclusion drawing, and data verification were conducted. Results: Out of the 11 studies included, nine were randomized controlled trials, and two were quasi-experimental studies. Among them, seven (63%) were conducted in HICs, and four (37%) were carried out in LICs. In both regions, the psychological aspect was the most commonly addressed subject in palliative care education for family caregivers. However, in LICs, no articles specifically addressed the social and spiritual aspects of family caregivers’ education. Research conducted in LICs mostly involved nurses, while studies in HICs included a more diverse range of healthcare professionals. Typically, these programs required two to three sessions, with 30-60 minutes duration for 3-12 weeks. Conclusion: The social and spiritual aspects can be integrated into family caregivers’ training programs in LICs in the near future. Nurses, as an integral part of the multidisciplinary team, are capable of contributing to the development of educational programs for family caregivers, especially in resource-limited countries where patients rely heavily on their caregivers and relatives. Support from nurses is fundamental in such contexts.